1997
DOI: 10.1111/j.1365-2133.1997.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of protoporphyrin IX fluorescence for condylomata after topical application of 5-aminolaevulinic acid: implications for photodynamic treatment

Abstract: To examine the potential of using photodynamic therapy (PDT) in condylomata, we studied the distribution and kinetics of protoporphyrin IX (PpIX) formation in condylomata acuminata and adjacent normal skin after topical application of 5-aminolaevulinic acid (ALA). PpIX fluorescence spectra were measured hourly in vivo after ALA application. After gross fluorescence imaging, the lesions were biopsied, and fluorescence microscopy was performed. All three PpIX fluorescence detection modalities suggested selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…Selective accumulation of PPIX fluorescence was demonstrated in the condylomata (117, 118). Chen et al (119) reported a randomized clinical trial comparing ALA-PDT vs. CO 2 laser vaporization in treatment of condylomata acuminata: Sixty-five patients were allocated to receive 20% ALA solution under occlusive dressing for 3 h followed by irradiation with the helium-neon laser at a dose of 100 J/cm 2 while patients were treated with the CO 2 laser.…”
Section: Pdt For Clinical Infectious Diseasementioning
confidence: 98%
“…Selective accumulation of PPIX fluorescence was demonstrated in the condylomata (117, 118). Chen et al (119) reported a randomized clinical trial comparing ALA-PDT vs. CO 2 laser vaporization in treatment of condylomata acuminata: Sixty-five patients were allocated to receive 20% ALA solution under occlusive dressing for 3 h followed by irradiation with the helium-neon laser at a dose of 100 J/cm 2 while patients were treated with the CO 2 laser.…”
Section: Pdt For Clinical Infectious Diseasementioning
confidence: 98%
“…Additionally, the photosensitizers fluoresce which can assist in the pretreatment localization of lesions. 8,156 Photodynamic therapy has also been used to treat common warts on the hand, flat warts and plantar warts. [157][158][159][160] …”
Section: Photodynamic Therapymentioning
confidence: 99%
“…126 Eradication of human papillomavirus in genital warts (condyloma acuminata) has been shown with use of PDT in conjunction with 5-ALA, Photolon™ (Belmedpreparaty, Minsk, Republic of Belarus), polyhematoporphyrin, and YAG-OPO laser irradiation or CO 2 laser vaporization. [127][128][129][130][131][132][133] Finally, there are reports of successful treatment with PDT for cases of molluscum contagiosum and herpes simplex virus. 134,135 In this setting, PDT is still working primarily in an antiproliferative manner.…”
Section: Pdt In Microbial Diseases Virusesmentioning
confidence: 99%